Relationship Between Energy, Fat, and Carbohydrate Consumption Habits in Pregnant Women Chronic Energy Deficiency during the COVID-19 Pandemic: A Systematic Review - Wahyu Trecy Indriani; Vitri Widyaningsih; Anik Lestari (Universitas Ahmad Dahlan, 2023)
Background: Chronic Energy Deficiency (CED) during the COVID-19 pandemic affects the nutritional status of pregnant women. CED is indicated by the size of LiLA < 23.5 cm. This study aims to improve the nutritional status of pregnant women with chronic energy deficiency. Method: The study used a systematic review of relevant articles from databases (Pubmed, ScienceDirect, and Google Scholar) using keywords in Indonesian and English. Nine articles were selected based on the following inclusion criteria: publication from 2017 to 2021, discussing food consumption habits in pregnant women, articles in English or Indonesian, full text, open access, and scientific journals.Â Results: The results of this study can evaluate the consumption habits of pregnant women CED caused by inadequate food intake and less diverse food. Less food consumption habits in pregnant women are caused by low family income, human resources, education, and lack of family support to consume nutritional food. Conclusion: The study concludes that adequate food intake and good human resource consumption habits can affect pregnant women's nutritional status.